Modeling sand slides by a mechanics-based degenerate parabolic equation. (August 2019) - Lo Giudice, A.; Giammanco, G.; Fransos, D.; Preziosi, L.
Avalanching plays a crucial role in granular materials dynamics, in particular in the evolution of the shape of the leeward side of sand dunes. This paper presents a physically-based mathematical model capable of reproducing the kinematic evolution of the surface of sand piles and to obtain eventually the stationary configurations, in the presence of external sources as well. Simulation results with different boundary conditions and geometries are reported in order to show the high flexibility of the model. The model is also validated by means of comparison with the experimental results of different authors.